The Effect of Animation Video Media Towards IPAS Learning Results at Grade IV SD Negeri 01 Ulak Karang Selatan - Yanda, Yilma; Stavinibelia, Stavinibelia (The Future of Education Journal, 2024)
This research aims to enhance the learning outcomes of students by using animated videos in learning the material. Theme 1: About the growth and development of living creatures, Subtheme 3: Metamorphosis of Animals, Learning 5. This purchase is a quasi-experimental study using animated video media conducted in two classes. The subjects in this study were students of class IV SDN 01 Ulak Karang Selatan, in class A, which numbered as many as 20 students, and in class B, which numbered 20 students. Student learning results are measured from the final test of student learning results. From the results of the research, it can be seen that the animated video media can improve the learning results of students in the learning process of IPAS in class IV SDN 01 Ulak Karang Selatan. This can be seen in the difference between the average value of the experimental pretest of 54.9 and the posttest experimental of 80.1, whereas the average evaluation of the control class pretest is 47.9 and the control class posttest is 58.75. As can be seen on the test hypothesis t that obtained significance sig. (2-tailed) 0,000 < 0,05, this is stated according to the basis of decision-making in an independent test sample t-test. Then it can be concluded that Ha is accepted annd Ho is rejected. So, the results of the research show that there is an influence of animated video media on the learning outcomes of IPAS in SDN 01 Ulak Karang Selatan